(untitled) (Indian Journal of Animal Production and Management, 2024)
Captive animal welfare can be described as a state where animals do not exhibit prolonged negative emotional states and is allowed to express its natural behaviour while maintaining homeostasis. Animals that have good mental health will engage with their environment more, be less aggressive, less fearful and are more peaceful, exploratory and active. Such animals will be always be at ease and adapt well with their surroundings. Environmental enrichment provides species appropriate challenges, opportunities and stimulation that promote a range of normal behaviour pattern in animals. Achieving this quality of welfare among captive wildlife has numerous limitations and obstacles that must be addressed by zoos and other captive facilities. This article explores the various welfare problems in the care and management of captive animals as well as their mitigation techniques and assessment of their efficiency.